Determining the relationship between stress and self-efficacy in teachers working with children with autism spectrum disorder in Enugu State, Nigeria - Onyishi, Charity N (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2024)
Purpose - This study investigates the relationship between teacher stress and self-efficacy, with gender as a moderating factor, among teachers working with children with autism spectrum disorder (ASD) in Enugu State, Nigeria. Method- A correlational survey research design was employed, guided by two research questions and hypotheses. The study sample comprised 300 teachers purposively selected from special and conventional schools across various educational levels in Enugu State. The participants included 133 (44.3%) males and 167 (55.7%) females. Data were collected using the Teachers' Sense of Efficacy Scale (TSES), with a reliability coefficient of 0.97, and the Rosenberg’s Teachers’ Stress Assessment Scale (RTSAS), with a reliability coefficient of 0.83. Both instruments contained 15 items measured on a four-point Likert scale. Results - The findings indicated a significant positive but weak relationship between teacher stress and self-efficacy among teachers handling children with ASD. This suggests that increased stress may correspond to increased self-efficacy levels, possibly due to the development of adaptive skills and functional coping mechanisms. Additionally, gender did not moderate this relationship, suggesting that observed differences in favor of males might be attributed to chance. Implications - The results highlight the importance of targeted support programmes for teachers working with children with ASD. Enhancing teacher self-efficacy while addressing stress levels can contribute to improved teaching outcomes and teacher well-being. Originality/Value - This study contributes to the understanding of the dynamics between stress and self-efficacy among teachers of children with ASD in a Nigerian context. It highlights the critical need for interventions tailored to this unique teaching environment. *** Tujuan - Penelitian ini menyelidiki hubungan antara stres guru dan efikasi diri, dengan gender sebagai faktor moderator, di antara guru yang bekerja dengan anak-anak dengan gangguan spektrum autisme (ASD) di Negara Bagian Enugu, Nigeria. Metode- Desain penelitian survei korelasional digunakan, dipandu oleh dua pertanyaan penelitian dan hipotesis. Sampel penelitian terdiri dari 300 guru yang dipilih secara purposif dari sekolah khusus dan sekolah konvensional di berbagai tingkat pendidikan di Negara Bagian Enugu. Para peserta terdiri dari 133 (44,3%) laki-laki dan 167 (55,7%) perempuan. Data dikumpulkan dengan menggunakan Teachers' Sense of Efficacy Scale (TSES), dengan koefisien reliabilitas sebesar 0,97, dan Rosenberg's Teachers' Stress Assessment Scale (RTSAS), dengan koefisien reliabilitas sebesar 0,83. Kedua instrumen tersebut berisi 15 item yang diukur dengan skala Likert empat poin. Hasil - Temuan menunjukkan adanya hubungan positif yang signifikan namun lemah antara stres guru dan efikasi diri di antara para guru yang menangani anak-anak dengan ASD. Hal ini menunjukkan bahwa peningkatan stres mungkin berhubungan dengan peningkatan tingkat efikasi diri, mungkin karena pengembangan keterampilan adaptif dan mekanisme koping fungsional. Selain itu, jenis kelamin tidak memoderasi hubungan ini, menunjukkan bahwa perbedaan yang diamati dalam mendukung laki-laki mungkin disebabkan oleh kebetulan. Implikasi - Hasil penelitian menyoroti pentingnya program dukungan yang ditargetkan untuk guru yang bekerja dengan anak-anak dengan ASD. Meningkatkan efikasi diri guru sambil mengatasi tingkat stres dapat berkontribusi pada peningkatan hasil pengajaran dan kesejahteraan guru. Keaslian/Nilai - Studi ini berkontribusi pada pemahaman tentang dinamika antara stres dan efikasi diri di antara para guru anak-anak dengan ASD dalam konteks Nigeria. Penelitian ini menyoroti kebutuhan kritis akan intervensi yang disesuaikan dengan lingkungan pengajaran yang unik ini.